Impact of Inflation, Interest Rates, and Exchange Rates on the Performance of the Indonesian Sharia Stock Index (ISSI) during the Period 2012-2022 - Laila Tiffany Hasibuan; Imsar Imsar; Muhammad Ikhsan Harahap (International Journal of Economics Development Research (IJEDR), 2023)
This study aims to analyze the effect of inflation, interest rates and exchange rates on the rate of the Indonesian Sharia Stock Index (ISSI) for the period 2012-2022. This research method uses quantitative with VAR data type which is causal-distributive in nature, meaning that research is conducted to analyze a past situation and determine the direction of causality of the relationship between independent variables, namely Inflation, Interest Rates, Exchange Rates, and the dependent variable, namely the Indonesian Sharia Stock Index (ISSI). The operational data used by this researcher uses time series data. This research uses a method using the Eviews 12 computer program (software) with the Vector Auto regressive (VAR) model. The results of this study indicate that Inflation has a significant effect on ISSI. Interest rates have no effect on the ISSI. Exchange Rate has no effect on ISSI. The implications of this study reveal that Inflation has a relationship that can affect the growth rate of the ISSI. In addition, the growth rate of the ISSI can be suppressed if inflation can be controlled and exchange rates to interest rates can stabilize the rate of inflation that can affect the ISSI.